Effect of using different particle sizes of sand as filter media for dewatering faecal sludge - Kuffour, A.R.; Awuah, E.; Anyemedu, F.O.K.; Strauss, M.; Koné, D.; Cofie, Olufunke O. (Elsevier, 2009)
This research is aimed at investigating the effect of different particle sizes of sand for the dewatering of faecal sludge with respect to the dewatering time, contaminant load in the percolate, rate of clogging and quantity of biosolids produced. Three filter media FM1, FM2 and FM3 were used to dewater the faecal sludge. The experiment was conducted on bench scale consisting of miniature drying beds. Six cycles of dewatering were run where FM1, FM2, and FM3 showed average dewatering times of 10, 10 and 9 days respectively without significant differences (p > 0.05). However the percolate quality showed significant differences between them in the removal of TS, TVS, SS, COD, DCOD and NH3-N with FM1 having the highest removal for each parameter. Accumulation of organic matter in the top 10 cm of the filter bed indicated that FM1 was least likely to clog and it also generated the highest quantity of biosolids.